PALEOGEOGRAPHIC RECONSTRUCTIONS AND BASINS DEVELOPMENT OF THE ARCTIC - Golonka J.; Bocharova N.Y.; Ford D.; Edrich M.E.; Bednarczyk J.; Wildharber J. (My University, 2003)
Paleogeographic maps were constructed to depict the Phanerozoic plate tectonic configuration, paleoenvironment and lithofacies. These maps illustrate the geodynamic evolution of the circum-Arctic region. The relationship of the continental configuration, lithofacies, tectonics and climate from the disassembly of Rodinia to the assembly and breakup of Pangea is clearly depicted on this series of reconstructions. The distribution of lithofacies shows climatic change associated with continental assembly and disassembly as well as with the steady northward drift of the continents.From a regional perspective the facies in basins along the circum-Arctic margin reflect various stages of geotectonic development. The assembly of continents contributed to the formation of foreland basins. The breakup of continents, especially of the Pangean supercontinent, generated basins related to rifting and passive margin development. The subduction zones are related to the back-arc basins. The inversion caused by ridge pushing played an important role in the basin evolution.
Keywords: Phanerozoic; Plate tectonics; Paleogeography; Arctic; Sea-level; Paleoclimate; Lithofacies